STRATEGIC ANALYSIS OF “LINTAS DENPASAR PAGI” RADIO PROGRAM AT RRI DENPASAR IN SERVING PUBLIC INTEREST - Yuni Wulandari; Ade Wahyudin (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2021)
Broadcast media has an important role in social life in Indonesia because broadcasting does not only act as an entertainment medium but provides information that is needed by the public. This is a challenge for LPP RRI where it is required to maintain its idealism and existence and attract the attention of listeners so that it can support and bridge the interests of the community. One interesting program is